2011
DOI: 10.1002/bab.30
|View full text |Cite
|
Sign up to set email alerts
|

Expression of biologically active human insulin‐like growth factor 1 in Arabidopsis thaliana seeds via oleosin fusion technology

Abstract: Novel protein expression in plant-based systems has become an important tool in producing and studying therapeutic proteins. Among many plant-based systems developed so far, oleosin fusion technology is one of the most cost-effective and convenient methods. In this study, an important therapeutic protein, human insulin-like growth factor 1 (hIGF-1), was expressed in Arabidopsis thaliana seeds via this technology. The plant bias codon usage-optimized hIGF-1 gene was fused to the C-terminal of A. thaliana 18.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The effect of the insulin-like protein and the active compounds such as flavonoids that found in A. thaliana caused a significant decrease in blood glucose levels in diabetic mice similar to that reported on the hypoglycemic activity of A. thaliana by Weili et al, who reported that an important therapeutic protein human insulin-like growth factor 1 (hIGF-1) called somatomedin C, was expressed in A. thaliana seeds via oleosin fusion technology [19].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The effect of the insulin-like protein and the active compounds such as flavonoids that found in A. thaliana caused a significant decrease in blood glucose levels in diabetic mice similar to that reported on the hypoglycemic activity of A. thaliana by Weili et al, who reported that an important therapeutic protein human insulin-like growth factor 1 (hIGF-1) called somatomedin C, was expressed in A. thaliana seeds via oleosin fusion technology [19].…”
Section: Discussionsupporting
confidence: 67%
“…Hypoglycemic Effect [ Table- 2] showed that the daily treatment with Arabidopsis thaliana ethanolic extract of 200 mg/kg b.w. led to a significant reduction in the blood glucose levels after 3, 6, 9 days of the treatment which recorded 192, 154, 132 mg/dl respectively.…”
Section: * (+) Means Positive Detection (-) Means Negativementioning
confidence: 99%
“…Several biotechnological applications have been developed by using the unique characteristics of oil bodies, such as new ingredients for flavoring or emulsifying agents, affinity matrices for enzyme fixation/purification, and expression/purification systems for producing recombinant proteins via transgenic plants [144][145][146][147][148][149][150][151][152][153][154]. Many applications related to the utilization of oil bodies have been patented [155][156][157][158][159][160][161][162][163].…”
Section: Artificial Oil Bodies In Biotechnological Applicationsmentioning
confidence: 99%
“…More simple and cost-effective approaches consist in the fusion of target molecules to oleosin proteins to enhance the accumulation of the target proteins onto the surface of the oil bodies. Although this approach is limited to oilseed crops, it was recently attempted to purify human insulin-like growth factor 1 (hIGF-1) from Arabidopsis seeds (Li et al, 2011).…”
Section: Non-chromatography Methodsmentioning
confidence: 99%